PENERAPAN MODEL PEMBELAJARAN SELF ORGANIZED LEARNING ENVIRONMENTS (SOLE) UNTUK MENINGKATKAN PEMAHAMAN MATERI MAHASISWA DALAM KEGIATAN PRESENTASI - Azizah, Naila Binta; Fauziah, Nasya Octavia; Sesar, Bunga Septiani; Sulisnah, Sulisnah; Sa’diyah, Siti Halimatu; Khaerunnisa, Arin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In the ever-evolving digital era, students' ability to understand and deliver material effectively through presentations has become an essential skill in the academic and professional world. However, there are still many students who have difficulty in understanding the material in depth, which has an impact on the quality of their presentations. Therefore, it is important for students to learn and understand in advance the material to be presented by applying the self-organized learning environments (SOLE) learning model. The purpose of this research is by applying the SOLE model is expected to improve students' understanding of the material. The research method used in this research is the literature study method. Data collection quoted from various sources such as articles. Data collection techniques by citing several relevant sources. The results of this study the Self Organized Learning Enviroment (SOLE) learning model can improve material understanding, learning independence, critical thinking and problem solving skills. Students are able to express themselves more straightforwardly and increase student confidence to present material during presentations. So it can be concluded that the Self Organized Learning Enviroment (SOLE) learning model can improve students' understanding of material in presentation activities.